2014
DOI: 10.1007/s10509-014-2188-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term periodicities in interplanetary, geomagnetic and solar phenomena during solar cycle 24

Abstract: In this paper we study the quasi-periodic variations of sunspot area/number, 10.7 cm solar radio flux, Average Photospheric Magnetic Flux, interplanetary magnetic field (B z ) and the geomagnetic activity index A p during the ascending phase of the current solar cycle 24. We use both Lomb-Scargle periodogram and wavelet analysis technique and find evidence for a multitude of quasi-periodic oscillations in all the data sets. In high frequency range (10 days to 100 days), both methods yield similar significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 76 publications
2
23
1
Order By: Relevance
“…Shortterm periodicities of solar wind parameters are reported by many researchers e.g., Mursula and Zieger (1996), Nayar et al (2002), Katsavrias et al (2012), Singh et al (2012), Kim and Chang (2014), Singh and Badruddin (2014), Chowdhury et al (2015). Short-term oscillations of galactic cosmic ray (CR) particles are reported by Mavromichalaki et al (2003), Alania et al (2008), Chowdhury et al (2010), Sabbah and Kudela (2011), Kudela (2012), Singh et al (2012), Modzelewska and Alania (2013), Singh and Badruddin (2015), while short-term oscillations of geomagnetic indices are reported by Nayar et al (2002), Singh and Badruddin (2014), Chowdhury et al (2015) and many others. The variability of cosmic rays near earth is summarized by Kudela (2012).…”
Section: Introductionmentioning
confidence: 90%
“…Shortterm periodicities of solar wind parameters are reported by many researchers e.g., Mursula and Zieger (1996), Nayar et al (2002), Katsavrias et al (2012), Singh et al (2012), Kim and Chang (2014), Singh and Badruddin (2014), Chowdhury et al (2015). Short-term oscillations of galactic cosmic ray (CR) particles are reported by Mavromichalaki et al (2003), Alania et al (2008), Chowdhury et al (2010), Sabbah and Kudela (2011), Kudela (2012), Singh et al (2012), Modzelewska and Alania (2013), Singh and Badruddin (2015), while short-term oscillations of geomagnetic indices are reported by Nayar et al (2002), Singh and Badruddin (2014), Chowdhury et al (2015) and many others. The variability of cosmic rays near earth is summarized by Kudela (2012).…”
Section: Introductionmentioning
confidence: 90%
“…Short‐term periods like 20, 26, 29, 30, 32, and 34 day of Bz were reported by Chowdhury et al (2015) during 2009 to August 2014; 13.9, 28, and 30 day periods of Bz by Katsavrias et al (2012) during 1964–2010; 1.9, 3.3, 4.2, 8.8, 9.5, 13.4, 13.8, 27.5, and 28.3 day periods by Singh and Badruddin (2015a, 2015b) during solar minimum; 29 day by Gavryuseva (2018) in 2003; 13.9, 14.3, 27.8; and 28.5 day periods by Tsichla et al (2019) during 1995–2018. Recently, 3.9, 2.8, 2.4, 2.2, and 1.8 day periods of various solar wind plasma and field parameters have been reported by Singh and Badruddin (2019a) during the polarity reversal periods and 1.7, 1.8, 2.2, 3.3, and 3.8 day periods during solar minimum (Singh & Badruddin, 2015a, 2015b).…”
Section: Introductionmentioning
confidence: 69%
“…The reason behind the presence of these periodicities in SSN and F10.7 solar flux is the internal magnetic dynamo action in the solar interior. It has been shown that some of these periods are present in the solar magnetic flux variations during solar cycle 24 and may differ from year to year (Chowdhury et al, 2015). Hence, it can be seen from Fig.…”
Section: δF =mentioning
confidence: 82%